PELATIHAN DAN PENYULUHAN HIV/AIDS PADA LELAKI BERISIKO TINGGI DI KOTA KENDARI - Adius Kusnan; La Ode Alifariki; Amiruddin Eso; La Ode Muhammad Sety (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2021)
Truck/angkot drivers, port workers and nightlife lovers are groups that are very vulnerable to contracting HIV/ADS. This is because this group is the closest and often interacts with prostitution sites that may have been infected. HIV/AIDS is a disease for which there is no cure and there is no vaccine that can prevent the attack of the HIV virus, so this disease is a disease that is very dangerous for human life both now and in the future. The method used in this community service activity is in the form of training and counseling to the community about preventing the transmission and consequences of HIV/AIDS and a participatory approach, meaning that participants are required to be active in participating in the activity. The competencies that will be formed are marked by indicators of increasing participants' knowledge about the prevention of transmission and consequences of HIV/AIDS. The objective of the Halu Oleo University internal partnership program is to increase knowledge on the prevention of transmission and consequences of HIV/AIDS. Locations of training and counseling activities will be held at night entertainment centers, Kendari and Kemaraya ports, where truck drivers from outside the area gather. Supporting facilities and infrastructure that will be prepared for meeting rooms, audio visuals, and human resources from the Kendari City Service and Kendari Class II Port Health Office, as well as community service lecturers from Halu Oleo University. before training and counseling, the dominant knowledge of participants was in the poor category as many as 23 people (76.7%), while after training and counseling the participants' knowledge increased to the dominant category of good as many as 28 people (93.3%). A comprehensive HIV prevention program should not only focus on prevention of HIV transmission but also on the maintenance of physical and mental health of individuals with HIV which is closely related to the stigma that exists in society Keywords: HIV/AIDS, Training, Counseling, High-Risk Men